Solution‐Phase Magnetic Mechanistic Study of Ni‐Seamed Pyrogallol[4]arene Nanocapsules Reveal Presence of Novel Cylindrical and Spherical Species. Issue 30 (21st April 2022) - Kumari, Harshita; Dennis, Cindi L.; Kline, Steven R.; Mossine, Andrew V.; Deakyne, Carol A.; Atwood, Jerry L.
Abstract: The magnetic properties of nickel‐seamed C ‐pyrogallol[4]arene (PgC3 Ni) hexamers and dimers are studied for the first time in solution. The combination of small‐angle neutron scattering and superconducting quantum interference device magnetometer measurements of the solution species reveal their paramagnetic and weakly antiferromagnetic behaviour. Surprisingly, the magnetic results indicated the presence of an unprecedented 13 Å‐radius species, larger than both the dimeric and hexameric nanocapsules with both octahedral and square‐planar metal centers. To confirm the presence of this novel species, we performed a mechanistic study of PgC3 Ni as a function of temperature and solvent and deduced the presence of two additional new species: a) an 11 Å cylinder with Ni atoms seaming the tubular framework and b) an 8 Å‐radius sphere with non‐interacting Ni centers located within the internal cavity. Select parameters that shift the equilibrium towards desired species are also identified. Abstract : First solution‐phase magnetic study of Ni‐seamed pyrogallol4]arene leads to the discovery of novel hydrogen‐bonded 8 Å‐radius dimeric sphere, Ni‐seamed 13 Å‐radius sphere and a Ni‐seamed 11 Å‐radius tubular nanoassemblies.